Reform of Law Enforcement to Strengthen the Legal System in Eradicating Money Laundering Through Cryptocurrency Investments - Rusman rusman; Zudan Arief Fakrulloh (Journal of Social Research, 2024)
Cryptocurrency investments are rapidly developing worldwide, including in Indonesia. Behind its profit potential, digital assets also open opportunities for criminals to commit money laundering offenses. The anonymity, pseudonymity, and decentralization of blockchain technology underlying cryptocurrencies create challenges for law enforcement in tracking illegal activities that exploit these assets. This study aims to examine the role of existing regulations in preventing the use of digital assets as a means of money laundering and to identify the challenges faced by law enforcement in enforcing rules against suspected cryptocurrency transactions. The research will analyze the extent to which the existing regulations, both at the national and international levels, are effective in preventing the use of cryptocurrencies for money laundering crimes. The second subtitle will explore various technical and legal constraints faced by law enforcement, including the lack of international cooperation, limitations of monitoring technology, and the low level of technical expertise among law enforcement officials.